Maternal Zinc Diet Impairs Learning and Memory in Offspring Rats through the CREB/BDNF Pathway - Novi Dewi Tanjung; Nieka Adhara Wahono; Ninik Mudjihartini; Ani Retno Prijanti (Indonesian Biomedical Journal, 2024)
BACKGROUND: Zinc released into the synaptic cleft able to modulate various signaling pathways, including brain derived neurotrophic factor (BDNF) and its receptor tropomyosin receptor kinase B (TrkB). Zinc binding to its receptor, G-protein coupled receptor 39 (GPR39), may trigger biochemical pathways leading to cAMP response element binding protein (CREB)-dependent gene transcription that subsequently promotes BDNF upregulation. Therefore, zinc dyshomeostasis should be considered as a condition that induces disruption of CREB/BDNF signaling. This study was conducted to examine the effect of maternal zinc diet on hippocampal expression levels of CREB and BDNF in offspring.